Kinetic Modeling of the Extraction–Oxidation Coupling Process for the Removal of Dibenzothiophene - Lu, Zongjing; Guo, Erliang; Zhong, Hua; Tian, Yajie; Yao, Yue; Lu, Shuxiang (Energy & fuels, 2016)
Extraction–oxidation desulfurization (EODS) technology would be a potential industrial application for achieving ultralow-sulfur fuel oils. A combined extraction–oxidation system for dibenzothiophene removal from model fuel with H2O2 as an oxidant, acetonitrile as an extractant, and Mo/γ-Al2O3 as a catalyst was performed in a batch reactor. To study this complex heterogeneous system, the chemical reaction and mass transfer on each phase were individually assessed. Kinetics of the EODS system for dibenzothiophene in model fuel was developed, comprising the chemical kinetic mechanism and mass transfer effects. The kinetic parameters of the kinetic model, such as the kinetic constants and apparent activation energy, were determined. The EODS system in the experimental condition is determined by both the extraction process and catalytic oxidation reaction, because the terms involving the intrinsic resistance of the chemical reaction are no more important than mass transfer resistance.